Effect of visual attention tasks on addiction research - İyilikci, Osman (Journal of Dependence, 2021)
In addiction research, a number of visual attention tasks are utilized as a measurement tool or an experimental technique. In this review, it is aimed to analyze the effect of common visual attention tasks on addiction research. In this frame, to what end the change detection task, dual task, attentional blink paradigm and Stroop test are utilized in addiction studies and main findings of those studies are summarized. From this point of view, it can be suggested that visual attention tasks are used to investigate individuals’ attentional bias for addicted object in addiction research, moreover, the effect of attentional bias in maintaining the dependence is emphasized. The potential of utilizing visual attention tasks in diagnosing and treating addiction is also emphasized in the literature.